An Analysis of Men’s Language Features of an Dark Action Comedy on Prime Video - Nugraha, Komang Yoga Artha; Sutjiati Beratha, Ni Luh; Suwari Antari, Ni Made (Humanis; Vol 28 No 3 (2024)DO - 10.24843/JH.2024.v28.i03.p02, 2024)
The purpose of the research titled "An Analysis of Gender in Language of a Dark Action Comedy on Prime Video" is to identify gendered language features applied in the series The data was collected using documentation method and was analyzed using qualitative method based on Jennifer Coates of men's language features as applied to the characters in the series "The Boys" episode 1 on Amazon Prime. The research identified several language features, including order versus proposal, swearing and taboo language, and interruptions, applied to the characters in the series. The main characters, Hughie and Hugh Campbell Sr., predominantly exhibited these features. Hughie used direct forms of address, swear words, and interruptions in his speech. Other characters in the series also displayed men's language features and differences in their language use.